Efficacy of endovascular treatment of meningiomas: evaluation with matched samples. - Dean, B L; Flom, R A; Wallace, R C; Khayata, M H; Obuchowski, N A; Hodak, J A; Zabramski, J M; Spetzler, R F (American Journal of Neuroradiology, 1994)
PURPOSE To evaluate the clinical efficacy, cost-effectiveness, and safety of presurgical devascularization of meningiomas. METHODS Matched samples of embolized and nonembolized groups of meningiomas were compared. The study variables for clinical efficacy were estimated blood loss, number of transfusions, surgical resection time, and length of hospitalization. The cost-effectiveness was evaluated by adjusting all hospital costs to 1991 dollar amounts, and adding additional embolization costs and fees to the hospital cost totals for the embolized group. A qualitative comparison of complications was made. RESULTS All dependent variables evaluating the clinical efficacy of the procedure (estimate blood loss, 533 cc versus 836 cc; number of transfusions, 0.39 units versus 1.56 units; surgical resection time, 305.8 minutes versus 337.5 minutes; and length of hospitalization, 10.6 days versus 15.0 days) displayed trends of higher means in the nonembolized group; however, only the estimated blood loss and number of transfusions variables were significant. The cost-effectiveness of the procedure was not statistically significant. The mean cost was $29,605 for the embolized group and $38,449 for the nonembolized group. There were three major and nine minor complications in the nonembolized group and zero major and six minor complications in the embolized group. There were four additional minor complications caused by the embolization procedure. CONCLUSION Endovascular devascularization of meningiomas is beneficial for large meningiomas because it diminishes the necessity of intraoperative transfusions and decreases blood loss. The additional day of hospitalization, emolization costs, and costs of complications do not conversely increase treatment costs. There were no major complications or adverse long-term effects caused by the embolization procedure.